Procyclicality in Central Bank Reserve Management : Evidence from the Crisis - Pihlman, Jukka; Hoorn, Han. (Washington, D.C. : International Monetary Fund, 2010)
A decade-long diversification of official reserves into riskier investments came to an abrupt end at the beginning of the global financial crisis, when many central bank reserve managers started to withdraw their deposits from the banking sector in an apparent flight to quality and safety. We estimate that reserve managers pulled around USD 500 billion of deposits and other investments from the banking sector. Although clearly not the main cause, this procyclical investment behavior is likely to have contributed to the funding problems of the banking sector, which required offsetting measures by other central banks such as the Federal Reserve and Eurosystem central banks. The behavior highlights a potential conflict between the reserve management and financial stability mandates of central banks. This paper analyzes reserve managers' actions during the crisis and draws some lessons for strategic asset allocation of reserves going forward.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet